2010
DOI: 10.1021/jf903701h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Melanoidins on Lipid Peroxidation during Simulated Gastric Digestion: Their Possible Role in the Prevention of Oxidative Damage

Abstract: The ability of high molecular weight melanoidins extracted from coffee, barley coffee, and dark beer to inhibit lipid peroxidation during simulated gastric digestion of turkey meat has been investigated. Results showed that melanoidins decrease the synthesis of lipid hydroperoxides and secondary lipoxidation products. Coffee melanoidins at 3 mg/mL reversed the reaction and broke down hydroperoxides to concentrations lower than the initial value. Barley coffee and dark beer melanoidins were less effective, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 35 publications
(57 reference statements)
10
86
0
4
Order By: Relevance
“…Vicente et al [40] demonstrated the increase of antioxidant enzyme activity in rats fed roasted coffee and postulated that coffee may reduce the overall oxidative stress and the risk of associated degenerative disorders. In another study, hydrophobic MRP was proved to inhibit in vitro and in vivo lipid peroxidation and formation of lipoxidation products [41]. In our study, hydrophobic MRP was contained in DiRCE, and the rats fed a diet supplemented with this extract had the lowest level of non-HDL cholesterol.…”
Section: Animal Studysupporting
confidence: 52%
“…Vicente et al [40] demonstrated the increase of antioxidant enzyme activity in rats fed roasted coffee and postulated that coffee may reduce the overall oxidative stress and the risk of associated degenerative disorders. In another study, hydrophobic MRP was proved to inhibit in vitro and in vivo lipid peroxidation and formation of lipoxidation products [41]. In our study, hydrophobic MRP was contained in DiRCE, and the rats fed a diet supplemented with this extract had the lowest level of non-HDL cholesterol.…”
Section: Animal Studysupporting
confidence: 52%
“…The mixture was incubated at 40°C in the dark for 7 days. The amount of generated lipid hydroperoxide was measured by the FOX assay as reported by Tagliazucchi et al (2010). The lipid peroxidation inhibitory activity of the samples was expressed as percentage of inhibition with respect to a control reaction without the sample.…”
Section: Abts + Radical Scavenging Activity Of Digested Samples and Amentioning
confidence: 99%
“…Several studies have shown that melanoidins extracted from different foods possess radical scavenger activity, metal chelating ability and lipid peroxidation inhibitory activity under gastro-intestinal physiological conditions (Goya et al 2007;Pastoriza and Rufián-Henares 2014;Tagliazucchi et al 2010).…”
Section: Antioxidant Properties Of Food Melanoidins In the Gastro-intmentioning
confidence: 99%
“…The excess of iron in the body causes several pathologies, because it becomes free from proteins and thus able to form reactive species and free radicals (Ronca et al 2003). Melanoidins with their capacity to chelate iron lead to a decrease in its bio-availability possibly reducing the oxidative stress in the gastro-intestinal tract and in the body (Mesías et al 2009b;Tagliazucchi et al 2010;Verzelloni et al 2010). In this regard, it has been shown that water-soluble high molecular weight melanoidins extracted from instant coffee and other foods are able to inhibit the formation of lipid hydroperoxide and advanced lipid oxidation end products (measured as TBA-RS) during simulated gastric digestion of turkey meat Verzelloni et al 2010).…”
Section: Antioxidant Properties Of Food Melanoidins In the Gastro-intmentioning
confidence: 99%
See 1 more Smart Citation